PENGARUH PENERAPAN TEKNOLOGI INFORMASI TERHADAP PENINGKATAN KEUNGGULAN KOMPETITIF PADA USAHA KEDAI KOPI DI KOTA BANDUNG - Kristoforus Farian Waringga; Fitria Dina Riana; Anisa Aprilia (Sepa, 2022)
A coffee shop is a business that is currently a very profitable choice so that it is increasingly popular with business people in Indonesia. Challenges arise due to the intense competition and environmental uncertainty in the market. Information technology becomes a bridge in order to have a more responsive, effective and efficient performance. This research was conducted with the aim of examining the effect of the application of information technology on increasing competitive advantage through supply chain performance variables, information sharing, and supply chain integration. In this study, 59 coffee shops located in Bandung were used as research samples. Furthermore, the data will be analyzed using SEM-PLS in order to know how the influence between variables using the WarpPLS v7.0 software. The results show that information technology has a significant effect on increasing competitive advantage through supply chain performance variables, information sharing, and supply chain integration. So, coffee shop owners or managers can improve their supply chain performance by utilizing information technology because information technology helps coffee shop businesses work effectively and efficiently, is more responsive, has an integrated work system and knows consumer needs because it can be closer to consumers